Analisis Sifat Kimia dan Evaluasi Kesuburan Tanah Pada Lahan Kering Di Kecamatan Eremerasa Kabupaten Bantaeng - Saida Saida; Ardiansyah Putra; Bakhtiar Ibrahim (Savana Cendana, 2023)
This study aims to determine the status of soil fertility on dry land, soil fertility parameters which are the limiting factors on dry land and make a map of soil fertility status in Eremerasa District, Bantaeng Regency. This research was conducted in Eremerasa Subdistrict, Bantaeng Regency, South Sulawesi and the Laboratory of Soil Science and Environmental Conservation, Faculty of Agriculture, Muslim University of Indonesia, and Soil Laboratory of the Faculty of Agriculture, Hasanuddin University, in February–August 2022. Data from the land use maps, soil type maps, slope maps, and soil fertility maps were collected using the PPT 1995 research technique. The two maps are juxtaposed. The soil response (pH), soil CEC, base saturation, phosphorus content, potassium content, and C-Organic are among the soil characteristics assessed in the laboratory and are all adjusted to the information provided. It is necessary to do a 1995 PPT method soil fertility evaluation. The data were gathered using both primary and secondary sources, and they were then modified to meet the 1995 PPT's recommendations for soil fertility. The results showed that the status of soil fertility in Eremerasa District, Bantaeng Regency was in the status of low to very low criteria. Soil fertility parameters that became obstacles in soil fertility status were cation exchange capacity, base saturation dominated by low criteria, and Phosphorus content which also had criteria. low, C-organic and Potassium with very low criteria and pH dominated by slightly acidic criteria. The research area with low soil fertility status is 2,611.92 ha, while the research area with very low soil fertility status is 72.96 ha.